The typology of Asian Englishes - Lim, Lisa; Gisborne, Nikolas, 1966- (Benjamins current topics ;, 2011)
When considering the structure of New Englishes which have evolved in - multilingual, mostly post-colonial - contexts of Asia (thus, Asian Englishes), the significant factors to be considered are: 1) the variety/ies of the English lexifier that entered the local context; 2) the nature of transmission of English to the local population; and 3) the local, i.e. substrate, languages of the community in which the New English emerges. This third factor is the focus of the five papers in this volume: they investigate the structure of Asian varieties of English by exploring the relationship between th.